1998
DOI: 10.1159/000007508
|View full text |Cite
|
Sign up to set email alerts
|

<i>Helicobacter pylori</i> Infection Decreases Gastric Alcohol Dehydrogenase Activity and First-Pass Metabolism of Ethanol in Man

Abstract: Background/Aims: Ethanol is metabolized by alcohol dehydrogenase in the human stomach. This metabolism contributes to the so-called first-pass metabolism of ethanol which is affected by gender, medication, and morphological alterations of the gastric mucosa. Recently, it has been shown that Helicobacter pylori is capable to oxidize ethanol to acetaldehyde in vitro. Since H. pylori also injures gastric mucosa, the present study examines the effect of this bacterium on gastric alcohol dehydrogenase activity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
19
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 33 publications
5
19
1
Order By: Relevance
“…When we measured total ADH activity in gastric mucosa we did not find significant differences between infected and noninfected samples [9]. In contrast, various authors have found a low gastric ADH activity in the presence of H. pylori infection [21][22][23]. In this study the total activity of ADH was significantly higher in sera of H. pylori-positive patients than in sera of controls.…”
Section: Discussioncontrasting
confidence: 73%
“…When we measured total ADH activity in gastric mucosa we did not find significant differences between infected and noninfected samples [9]. In contrast, various authors have found a low gastric ADH activity in the presence of H. pylori infection [21][22][23]. In this study the total activity of ADH was significantly higher in sera of H. pylori-positive patients than in sera of controls.…”
Section: Discussioncontrasting
confidence: 73%
“…However, the change of class IV ADH isoenzyme activity was not accompanied by the change in total ADH activity. Other authors, who measured total ADH activity with ethanol as a substrate, showed the decrease of enzyme activity in H. pylori -positive samples [8, 9, 10]. …”
Section: Discussionmentioning
confidence: 99%
“…According to various authors, the gastric ADH activity was significantly lower in the presence of H. pylori infection [8, 9, 10]. It was also documented that chronic gastritis associated with H. pylori predominates in the antrum of the stomach [8, 9, 10, 11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observation which we found is compatible to the report of Simanowski et al, who showed that mucosal ADH activity and first-pass metabolism of alcohol were reduced in subjects with H. pylori infection of the gastric mucosa when compared with those in non-infected subjects. 21 They evaluated first-pass metabolism by measuring the systemic availability of ethanol after administration of ethanol (0.225 g/kg body weight) either orally or intravenously. This dose is approximately 200-times higher than that employed in the present study in 60-kg body weight subjects.…”
Section: Discussionmentioning
confidence: 99%